The Power of Constitutional Court to Settle Disputes on Local Election Results : Kewenangan Mahkamah Konstitusi Memutus Perselisihan Hasil Pemilihan Kepala Daerah - I Dewa Gede Palguna; Bisariyadi Bisariyadi (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
Constitutional Court Decision No. 85/PUU-XX/2022 abolished the proposal to establish a special court that have the power to resolve disputes on local election. As a result, that power shifted to Constitutional Court. This, de facto, is not the power designed to be exercised by the Court. Back tracked on historical trajectory of holding direct local elections, there has been a tug-of-war between judicial bodies on who have the legitimate power to settle the disputes on local elections results. This study aims to examine the power of Constitutional Court to adjudicate disputes on local election results. To achieve the research objective, this research framework will look at the historical context to have an overview of the dynamics of transposition of judicial bodies to settle the disputes. In addition, this also assess Constitutional Court decisions which provide interpretations as the basis for the legitimacy of the Court's power to adjudicate local election disputes.